Rational Design of Nanobody80 Loop Peptidomimetics: Towards Biased β2 Adrenergic Receptor Ligands. Issue 40 (29th June 2017) - Martin, Charlotte; Moors, Samuel L. C.; Danielsen, Mia; Betti, Cecilia; Fabris, Cecilia; Sejer Pedersen, Daniel; Pardon, Els; Peyressatre, Marion; Fehér, Krisztina; Martins, José C.; Mosolff Mathiesen, Jesper; Morris, May C.; et al.
Abstract: G protein‐coupled receptors (GPCRs) play an important role in many cellular responses; as such, their mechanism of action is of utmost interest. To gain insight into the active conformation of GPCRs, the X‐ray crystal structures of nanobody (Nb)‐stabilized β2 ‐adrenergic receptor (β2 AR) have been reported. Nb80, in particular, is able to bind the intracellular G protein binding site of β2 AR and stabilize the receptor in an active conformation. Within Nb80, the complementarity‐determining region 3 (CDR3) is responsible for most of the binding interactions. Hence, we hypothesized that peptidomimetics of the CDR3 loop might be sufficient for binding to the receptor, inhibiting the interaction of β2 AR with intracellular GPCR interacting proteins (e.g., G proteins). Based on previous crystallographic data, a set of peptidomimetics were synthesized that, similar to the Nb80 CDR3 loop, adopt a β‐hairpin conformation. Syntheses, conformational analysis, binding and functional in vitro assays, as well as internalization experiments, were performed. We demonstrate that peptidomimetics can structurally mimic the CDR3 loop of a nanobody and its function by inhibiting G protein coupling as measured by partial inhibition of cAMP production. Abstract : Looping out : Cyclic peptidomimetics were designed as potential tools to structurally mimic the CDR3 loop of nanobodies (see figure). Herein, the synthesis, conformational analysis, binding, and functional in vitro assays are presented, together demonstrating that a single CDR3 loop mimetic could not functionally mimic the parent nanobody.